Strategic Development of Tree Resistance Against Forest Pathogen and Insect Invasions in Defense-Free Space - Showalter, David N.; Raffa, Kenneth F.; Sniezko, Richard A.; Herms, Daniel A.; Liebhold, Andrew M.; Smith, Jason A.; Bonello, Pierluigi (Frontiers in Ecology and Evolution, 2018)
• Invasive pathogens that cause stem cankers and wilts of trees, and insects that bore into bark and wood have proven extremely destructive to the world’s forests and particularly difficult to manage once established • Such pests are especially devastating when evolutionarily naïve host trees lack adequate natural defenses • Modern tree improvement programs are increasingly capable of restoring such defenses and providing trees for planting that are capable of withstanding alien insects and pathogens • Careful target selection, early implementation and sustained support of these programs are important for their success • We provide a simplified framework to guide responses to invasive insects and pathogens and rapidly identify promising pests to target for development of host resistance